Galaxy Zoo: Exploring the Motivations of Citizen Science Volunteers - Raddick, M; Bracey, G; Gay, P; Lintott, C; Murray, P; Schawinski, K; Szalay, A; Vandenberg, J (2009)
The Galaxy Zoo citizen science website invites anyone with an Internet connection to participate in research by classifying galaxies from the Sloan Digital Sky Survey. As of April 2009, more than 200,000 volunteers had made more than 100 million galaxy classifications. In this paper, we present results of a pilot study into the motivations and demographics of Galaxy Zoo volunteers, and define a technique to determine motivations from free responses that can be used in larger multiple-choice surveys with similar populations. Our categories form the basis for a future survey, with the goal of determining the prevalence of each motivation.